2012
DOI: 10.1109/tpami.2011.217
|View full text |Cite
|
Sign up to set email alerts
|

Constrained Nonnegative Matrix Factorization for Image Representation

Abstract: Nonnegative matrix factorization (NMF) is a popular technique for finding parts-based, linear representations of nonnegative data. It has been successfully applied in a wide range of applications such as pattern recognition, information retrieval, and computer vision. However, NMF is essentially an unsupervised method and cannot make use of label information. In this paper, we propose a novel semi-supervised matrix decomposition method, called Constrained Nonnegative Matrix Factorization (CNMF), which incorpor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
230
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 437 publications
(248 citation statements)
references
References 24 publications
0
230
0
Order By: Relevance
“…These NMF methods, which are referred as unsupervised learning methods, are not optimal to many real-world problems where limited knowledge (such as label information) from domain experts is available. To address this limitation, Liu et al [2] extended NMF to the semi-supervised setting and proposed the constrained NMF (CNMF). It takes the label information as hard constraints by enforcing data with the same label to have the same new representations, thus, the obtained representations may have more discriminating power.…”
Section: Related Workmentioning
confidence: 99%
See 2 more Smart Citations
“…These NMF methods, which are referred as unsupervised learning methods, are not optimal to many real-world problems where limited knowledge (such as label information) from domain experts is available. To address this limitation, Liu et al [2] extended NMF to the semi-supervised setting and proposed the constrained NMF (CNMF). It takes the label information as hard constraints by enforcing data with the same label to have the same new representations, thus, the obtained representations may have more discriminating power.…”
Section: Related Workmentioning
confidence: 99%
“…Similar to the experimental setting in [2], we conduct the experiments for each method on the different number of clusters from 2 to 10 to make a thorough comparison. For a fixed cluster number k, we randomly choose k categories from the dataset, and mix the images of these k categories as the collection V for clustering.…”
Section: Face Clusteringmentioning
confidence: 99%
See 1 more Smart Citation
“…Donoho and Stodden showed that NMF only gives the exact and unique solution for certain classes of partsbased data-sets [6]. Nevertheless, the popularity of NMF in recent years has grown unabated due to the simplicity of its updates and the success of its application in areas such as bioinformatics [8] and computer vision [9]. In this paper, we consider Donoho and Stodden's parts-based explanation for the success of NMF and posit that there exists, in some sense, an even simpler representation of the data.…”
Section: Bibt E Xmentioning
confidence: 99%
“…Usually, exploiting label information in the framework of NMF can allow obtaining discriminative information. For example, Liu et al [9] proposed Constrained Nonnegative Matrix Factorization (CNMF), which imposes the label information for the objective function as hard constraints. Li et al [10] developed a semi-supervised robust structured NMF, which exploited the block-diagonal structure in the framework of NMF.…”
Section: Introductionmentioning
confidence: 99%